Severe Sepsis Associated with Lemierre’s Syndrome: A Rare but Life-Threatening Disease - Audrey Tawa; Raphaëlle Larmet; Yannick Malledant; Philippe Seguin (Case Reports in Critical Care)
Background. The incidence of Lemierre’s syndrome has increased in the past decade. This posttonsillitis complication may be life threatening. Case Presentation. A 19-year-old patient was admitted to Surgical Intensive Care Unit of a French University Hospital for high fever, low blood pressure, and haemoptysis following a sore throat episode. Blood analysis revealed a thrombopenia, an acute renal failure, and an elevated lactate serum. Fusobacterium necrophorum was found in blood cultures. Computed tomography of the neck and lungs confirmed the diagnosis of Lemierre’s syndrome: pleural effusions, bilateral lung infiltrates, and an internal jugular vein thrombosis. Fluid administration and antibiotic treatment were quickly initiated. Patient left the unit four days after his admission without any organ dysfunction. Conclusion. Lemierre’s syndrome may lead to multiorgan dysfunction and should be rapidly identified.